LIMBERG’S FLAP: OUR EXPERIENCE OF 50 PATIENTS AT MTH - Nazim Hayat; Saira Saleem (Journal of University Medical & Dental College, 2016)
ABSTRACT OBJECTIVE: To determine the results of Limberg’s ﬂap procedure in pilonidal sinus in terms of procedural safety and complications. STUDY DESIGN: A prospective analytical study PLACE AND DURATION OF STUDY: Study was conducted in surgical department of Madinah Teaching Hospital Faisalabad for one and a half year. METHODALOGY: In this study 50 consecutive patients of pilonidal sinus who underwent Limberg ﬂap procedure were included. After discharged from ward follow up visit was done on weekly basis stfor 1 month and monthly for next six month. KEY WORDS: Pilonidal sinus, Limberg’s ﬂap, Rhomboid ﬂap RESULTS: Out of 50 patients operated 47 (94%) were male and 3 (6%) were female (table 1). The age of patients ranged from 20-40 years with the median age of 25 years. All were operated electively after preparing for anesthesia. Rhomboid excision with Limberg ﬂap reconstruction was done (Fig. 1-4). All were followed in outdoor after discharged from ward. Morbidity developed in 3 patients (infection in one, one having wound seroma formation and only one came with recurrence (table 2). Not a single patient were having ﬂap necrosis or wound dehiscence. Almost all patients were pain free and all of them returned to work after treatment for their complication. The average hospital stay was 4-5 days and returned to work was after 15 days. CONCLUSION: Limberg Flap reconstruction with rhomboid excision technique of treating sacrococcygeal pilonidal sinus is beneﬁcial in chronic cases with minimal recovery time and early return to work.